Weak Form Efficiency of Pakistan Stock Market using Non-Parametric Approaches - Irfan, Muhammad; ., Maria Irfan (Journal of Social and Development Sciences, 2011)
This paper studies the performance of Karachi Stock Exchange (KSE) of Pakistan via nonparametric approaches. The study includes the weekly open and closing prices of KSE- 100 indexes for the period of 1st January 1999 to 31st August 2009. Several non-parametric approaches including KolmogorovSmirnov test (Lilliefors test), Ryan-Joiner test (Shapiro-Wilk), Anderson-Darling test, Phillips Perron (PP) unit root test and Runs test are used to test the conviction of the KSE stock market. All non-parametric tests graphically and numerically inform us that both return series do not follow the assumption of normality and randomness, which means rejecting the hypothesis of weak form of efficiency. Generally, results from the observed analysis strongly recommend that the Karachi Stock Market of Pakistan is not efficient.